Influência de variáveis de sinterização na microestrutura e propriedades mecânicas de peças de PTFE moldadas por prensagem isostática - Strabelli, Patrícia Giunchetti (2014)
Polytetrafluorethylene (PTFE) is used in a wide range of critical applications because of its outstanding chemical and thermal resistance, low surface energy and special tribological properties. Because of its ultra high molecular weight, which leads to high melt viscosity, PTFE cannot be processed by traditional extrusion and injection methods. Cold pressing followed by sintering above its melt temperature is the main processing technique. The sintering time is defined according to the dimensions of the manufactured part and may last from a few hours to several days for large parts. Studies of the influence of sintering time and temperature on PTFE crystalline microstructure and mechanical properties are scarce in the scientific literature, being the main objective of this study. PTFE plaques were isostatically pressed and sintered at temperatures from 360XC and 390XC for times between 10 e 10:000min. Differential Scanning Calorimetry (DSC), measurements of mass loss and density, Scanning Electron Microscopy (SEM), compression and tensile tests were performed. The results of mass loss demonstrated that degradation is more pronounced in the surfaces of the PTFE parts and increases with sintering time and temperature. Analysis of the enthalpies of fusion and density measurements indicated indirectly the reduction in the molecular weight and increase in the crystallinity degree with increasing sintering temperature and time. The SEM analysis allowed the direct observation of crystalline microstructure, indicating a trend of increasing of the width the crystalline lamellae with sintering time and temperature. Tension and compression tests have shown that even under a wide range of sintering conditions, for which the polymer molar mass, crystallinity degree and structure are modified, PTFE mechanical properties are not significantly affected. The results obtained will guarantee PTFE parts processors and users to rely on polymer performance, even for parts exposed to extreme sintering conditions, current found in the industry.